Recollections and taxo-ecological studies of Coleochaete scutata Bréb., Coleochaete pseudosoluta Gauthier-Lièvre and Coleochaete conchata Möb., West Bengal, India - Halder, Nilu (Nepalese Journal of Biosciences, 2015)
The present work had been carried out from Hooghly district, West Bengal, India in order to explore species diversity of the taxon Coleochaete Bréb. of the family Coleochaetaceae under the order Chaetophorales belonging to the class Chlorophyceae. There were some structural complexities and variations among the species. A total number of three species namely Coleochaete scutata Bréb., Coleochaete pseudosoluta Gauthier-Lièvre and Coleochaete conchata Möb. were collected and identified first time from this area. They were described with illustrations and some other valuable information. Shape, size and colour of vegetative and reproductive cells or structures were considered as taxonomic parameters for their identifications. Among them, Coleochaete scutata Bréb. was very common while other two species were rare in occurrence in this district. They are all epiphytes on submerged angiospermic plants. Perusal of cited literatures revealed that the above mentioned species were third time reports from West Bengal, India. Limnological study of water analysis showed that water was weakly alkaline and the aquatic ecosystems were oligotrophic and monomictic types.